2016
DOI: 10.1148/radiol.2016151289
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Extracellular Volume Fraction with Dual-Energy Equilibrium Contrast-enhanced Cardiac CT in Nonischemic Cardiomyopathy: A Prospective Comparison with Cardiac MR Imaging

Abstract: Purpose To evaluate the feasibility of equilibrium contrast material-enhanced dual-energy cardiac computed tomography (CT) to determine extracellular volume fraction (ECV) in nonischemic cardiomyopathy (CMP) compared with magnetic resonance (MR) imaging. Materials and Methods This study was approved by the institutional review board; informed consent was obtained. Seven healthy subjects and 23 patients (six with hypertrophic CMP, nine with dilated CMP, four with amyloidosis, and four with sarcoidosis) (mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(127 citation statements)
references
References 25 publications
5
111
0
11
Order By: Relevance
“…There is now emerging evidence suggesting dual energy and spectral CT may also be used to measure the iodine concentration in the myocardium using a delayed phase scan and thus derive the extracellular volume. Provisional studies demonstrate good agreement with CMR in patients with hypertrophic and dilated cardiomyopathies along with cardiac amyloidosis and sarcoidosis …”
Section: Myocardial Tissue Characterizationmentioning
confidence: 82%
“…There is now emerging evidence suggesting dual energy and spectral CT may also be used to measure the iodine concentration in the myocardium using a delayed phase scan and thus derive the extracellular volume. Provisional studies demonstrate good agreement with CMR in patients with hypertrophic and dilated cardiomyopathies along with cardiac amyloidosis and sarcoidosis …”
Section: Myocardial Tissue Characterizationmentioning
confidence: 82%
“…In order to evaluate the ischemic status of the bilateral leg precisely, we used dual-energy dual-layer spectral computed tomography (IQon Spectral CT; Philips Healthcare, Cleveland, OH, USA) and calculated extracellular volume fraction (ECV) scores (Supplementary Figure 3). 1 ECV is considered to expand in association with diffuse muscle fibrosis or infiltrates. By calculating ECV score, we succeeded in distinguishing the necrotic status of the muscle objectively.…”
Section: Supplementary Filesmentioning
confidence: 99%
“…In such cases, it has been demonstrated that among patients with HCM, patients with DCM, cardiac amyloidosis, and sarcoidosis there is higher myocardial extracellular volume fraction at dual-energy equilibrium contrast-enhanced CCT in per-segment analysis, which is in good agreement with CMR and suggests the potential of myocardial tissue characterization with CCT. 155…”
Section: Ancillary Imaging In Cardiomyopathymentioning
confidence: 99%